Case report: EML4::NTRK3 gene fusion in a patient with metastatic lung adenocarcinoma successfully treated with entrectinib - Lazzari, Chiara; Pecciarini, Lorenza; Doglioni, Claudio; Pedica, Federica; Gajate, Ana Maria Samanes; Bulotta, Alessandra; Gregorc, Vanesa; Cangi, Maria Giulia (Frontiers in Oncology, 2022)
Rearrangements involving the neurotrophin kinase (NTRK) genes NTRK1, NTRK2 and NTRK3 with different fusion partners have been observed in both adult and pediatric solid tumors. Larotrectinib and entrectinib have been the first tumor-agnostic compounds approved for the treatment of NTRK fusion-positive tumors. Here, we report the first case of a female patient with a diagnosis of stage IV lung adenocarcinoma harboring the EML4::NTRK3 gene fusion, and successfully treated with entrectinib.